Takeovers and Countering Short-termism in Target Boardrooms - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2013)
This article considers the extent to which UK company law and takeover regulation may have contributed to the supposed short-termism exercised by target directors in takeovers, that is, target directors focusing only on short-term financial gain to the current shareholders, rather than the target’s long-term wealth creation or the interests of other stakeholders. This article argues that general company law and takeover regulation do not mandate target directors to strictly prioritise the short-term financial interests of the company. While company law and takeover regulation require the target board to consider stakeholders’ interests, neither shareholders nor stakeholders have an enforceable right of action against the directors in connection with their failure to do so. This article suggests a partial solution to resolve the enforcement issue in relation to schemes of arrangement, while preserving the existing shareholder-centric model, and addresses the question of whether there is a need for a fundamental overhaul of company law and takeover regulation.